THE LEADERSHIP STYLE OF THE HEAD OF MADRASAH IN THE PERSPECTIVE OF PSYCHOLOGY TOWARDS IMPROVING THE PERFORMANCE OF MI NURUL HUDA 2 TEACHERS IN MOJOKERTO CITY - Maylita Dwi Putri; Muhammad Nasiruddin; Moh. Fatkur Rohman (AFHAM : Jurnal Pendidikan dan Keguruan, 2026)
This study aims to describe the leadership style of the madrasah principal from a psychological perspective on teacher performance. This research uses a qualitative approach with a descriptive method through observation, interviews, and documentation techniques. The results show that the principal applies an authoritarian and centralized leadership style characterized by centralized decision-making, strict supervision, and strong discipline enforcement for teachers in both academic and non-academic activities. Teachers are required to comply with all established policies, such as punctuality, completeness of teaching administration, and active participation in school activities. Violations of rules are sanctioned with warnings and written reprimands. This leadership style has an impact on improving teacher discipline and performance, but it also limits participation and communication opportunities. Therefore, it can be concluded that the principal’s leadership style is fairly effective in improving teacher performance, although it needs to be balanced with a more communicative and humanistic approach.